Rhinovirus infection of allergen-sensitized and -challenged mice induces eotaxin release from functionally polarized macrophages - Nagarkar, Deepti R. (2010)
Human rhinovirus is responsible for the majority of virus-induced asthma exacerbations. To determine the immunologic mechanisms underlying rhinovirus-induced asthma exacerbations, we combined mouse models of allergic airways disease and human rhinovirus infection. We inoculated ovalbumin-sensitized and challenged BALB/c mice with rhinovirus serotype 1B, a minor group strain capable of infecting mouse cells. Compared to sham-infected, ovalbumin-treated mice, virus-infected mice showed increased lung infiltration with neutrophils, eosinophils and macrophages, airway cholinergic hyperresponsiveness, and increased lung expression of cytokines including eotaxin-1/CCL11, IL-4, IL-13 and IFN-γ. Administration of anti-eotaxin-1 attenuated rhinovirus-induced airway eosinophilia and responsiveness. Immunohistochemistry showed eotaxin-1 in the lung macrophages of virus-infected, ovalbumin-treated mice, and confocal fluorescence microscopy revealed co-localization of rhinovirus, eotaxin-1 and IL-4 in CD68-positive cells. RV inoculation of lung macrophages from ovalbumin-treated, but not PBS-treated, mice induced expression of eotaxin-1, IL-4, and IL-13 ex vivo. Macrophages from ovalbumin-treated mice showed increased expression of arginase-1, Ym-1, Mgl-2 and IL-10, indicating a shift in macrophage activation status. Depletion of macrophages from ovalbumin-sensitized and -challenged mice reduced eosinophilic inflammation and airway hyperreactivity following RV infection. We conclude that augmented airway eosinophilic inflammation and hyperresponsiveness in RV-infected mice with allergic airways disease is directed in part by eotaxin-1. Airway macrophages from mice with allergic airways disease demonstrate a change in activation state characterized in part by altered eotaxin and IL-4 production in response to RV infection. These data provide a new paradigm to explain RV-induced asthma exacerbations.